Legal experience of the United States of America in the issue of space commercialization (Journal of actual problems of jurisprudence, 2021)
What is space now? What benefits can it bring to humanity and who is most interested in its development? Today, the history of the development of world cosmonautics shows that States at the dawn of space exploration pursued primarily a scientific and research goal for the implementation of their military and strategic tasks. The main feature of modern space activity is its active commercialization. Currently, commercial activities in outer space involve not only States, State institutions and international governmental organizations, but also private enterprises, as well as non-governmental organizations. Now space is a huge space for profit and its new participant is the private sector. It was private companies that began to invest huge amounts of money in the space sector. Today, the United States of America (USA) is a confident leader in the number of companies involved in space exploration. The comfortable development of the space business in the US is the result of a systematic, purposeful policy of the US in space exploration and profit from the work carried out, as well as the result of the legislative work of the state. Given the above, the practice and experience of the United States in the issue of space commercialization is of not only scientific, but also practical interest. The article is devoted to the international legal experience of the US in the issue of space commercialization. The authors analyze the main regulatory legal documents of the United States adopted since the beginning of space exploration, which contributed to the process of commercialization of space and space technologies, thereby contributing to the development of the state’s economy as a whole. Key words: space, space law, private space, US space.